Optimizing GISTARU: Evaluating a GIS-Based Platform’s Contribution to Indonesian Spatial Planning for Smart City Development - Rachmawati, Rini; Ghiffari, Rizki Adriadi; Wijdani, Ach Firyal; Qonita, Maryam; Tania, Novirene; Pigawati, Bitta (Department of Urban and Regional Planning, Diponegoro University, 2024)
GISTARU (Geographic Information System for Spatial Planning) is a web-based and GIS-based information system in Indonesia that makes it easy for the public to access spatial information. In GISTARU, there are an Online Spatial Plan (RTR Online) and an Interactive Detailed Spatial Plan (RDTR) application. This research aims to; Identify and analyze the use of the Online Spatial Plan (RTR Online) website and Interactive Detailed Spatial Planning (RDTR Interactive) application in GISTARU and as well as identify the requirements for developing the website and application. In addition, the research outcomes are analyzed in terms of their contribution to the development of smart cities. Data was collected through in-depth interviews and website searches related to GISTARU, RTR Online, and RDTR Interactive at the national, provincial, and district or city levels. In-depth interview analysis is carried out through selected cases. The results showed that most regions in Indonesia have an integrated spatial pattern with GISTARU. However, there were inconsistencies in the RTR Online and RDTR Interactive data entry in GISTARU. In the meantime, relatively few spatial structure data are integrated with RTR Online. The Interactive Detailed Spatial Plan application is now operational in the majority of Indonesian provinces. The only province in which all regions have implemented interactive RDTR is DKI Jakarta. This Geographic Information System for Spatial Planning is very useful for achieving the goal of smart cities, particularly related to public services in the smart governance dimension.